Quality Equivalence Across Diverse Learning Contexts: A Comparative Study of Project-Based Learning from a Deep Learning Perspective - Rosi Octariantoni; Rita Kurnia; Daviq Chairilsyah; Erna Budiarti; Ardianti; Reni Jati Putri Lestari; Dewi Susanti (Jurnal PAJAR (Pendidikan dan Pengajaran), 2026)
This study aimed to analyze the implementation of Project-Based Learning (PjBL) in public and private vocational schools from a deep learning perspective. The study was conducted at Muhammadiyah 2 Vocational School, Pekanbaru, a private school, and Public Vocational School 1, Pucuk Rantau, a state school. This research employed a comparative qualitative approach using observation, interviews, and documentation as data collection techniques. The findings revealed that the implementation of PjBL in both schools demonstrated different characteristics influenced by school environment, student characteristics, learning facilities, and educational orientation. At Muhammadiyah 2 Vocational School, Pekanbaru, PjBL focused more on social projects, character development, empathy, and students' social awareness. Meanwhile, at Public Vocational School 1 Pucuk Rantau, PjBL emphasized production skills, entrepreneurship, and the utilization of local potential through practice-based learning activities. The findings also indicated that PjBL positively influenced students' social attitudes, creativity, learning motivation, 21st-century skills, and critical thinking abilities in both schools. From a deep learning perspective, students were able to connect knowledge with real-life experiences and authentic contexts through meaningful project activities. Although the schools adopted different project orientations, they successfully created active, contextual, and authentic learning experiences through Project-Based Learning.